Optimalisasi Portofolio Saham Berbasis Green Economy: Analisis Sharpe Ratio, Treynor Ratio, Jensen’s Alpha, dan Korelasi ESG Score - Febrianti, Werry; Yaqin, Ainol (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2025)
Investments that incorporate Environmental, Social, and Governance (ESG) principles are increasingly recognized as a strategic approach to support the transition toward a green economy. This study aims to optimize a stock portfolio composed of constituents from the IDX ESG Leaders index by employing three performance evaluation indicators: Sharpe Ratio, Treynor Ratio, and Jensen’s Alpha. Five stocks—ADRO, INKP, EXCL, BFIN, and KLBF—were selected based on strong ESG scores, large market capitalizations, and consistent inclusion in the ESG index for the past two consecutive years. The data used consist of daily closing prices from January 2021 to April 2025, with the BI 7-Day Reverse Repo Rate serving as a proxy for the risk-free rate. The results indicate that certain ESG-based portfolios can deliver competitive risk-return performance, with ADRO and KLBF exhibiting superior Sharpe Ratios and positive Jensen’s Alpha values compared to the other stocks. These findings reinforce the role of ESG in constructing investment portfolios that are not only financially viable but also aligned with long-term sustainability goals.